RANCANG BANGUN APLIKASI PEMBELAJARAN JARINGAN KOMPUTER PADA ANDROID (Information Technology and Telematics, 2014)
Abstract:The rapid world of computer network technology makes information increasingly important to learn . we are a growing force in the world of informatics to understand the structuring of network systems ranging from network types , network architecture components required to build a network . With the establishment of a computer network learning application that runs on smart phones with Android operating system is expected to facilitate the users in learning the computer network that can be used anytime and anywhere. Research of computer network learning application that contains the material content of each meeting , accompanied by questions as a starting measuring the success of understanding the network , about the content and application assistance . created using HTML listings that can be run on android smart phone by calling the name of the file along with the file format of the application through a program that is in the file java android .Keywords:learning applications, network learning,computer networks.